G453(P) Management of kawasaki disease in a district general hospital. is there an optium aspirin dose?. (27th April 2015) - Murtagh, K; Damda, F
Abstract : Aims: Kawasaki disease (KD) is the commonest cause of paediatric acquired heart disease in the UK. Early treatment significantly reduces coronary artery complications. This study aimed to identify cases of KD presenting to our district general hospital (DGH). We wished to see how well diagnosis and management adhered to local guidelines. Methods: Retrospective review of case notes of patients admitted to our district general and diagnosed with KD between October 2011 and October 2014. Diagnosis and management was compared to local guideline. Results: Eighteen KD patients of variable age (3 months to 9 years) and ethnicity were identified. Two thirds of cases had incomplete KD. All had a history of fever >5 days. Diagnostic features included conjunctivitis (16/18); mucosal changes (15/18); rash (11/18); cervical lymphadenopathy and peripheral extremity changes (8/18). Irritability was a common feature. BCG scar changes were also present (2/18). All cases received intravenous immunoglobulin (IVIG) at 2 g/kg and high dose aspirin at 30–100 mg/kg/day except one who received aspirin alone as afebrile at presentation. Five patients had suspicion of coronary artery dilatation/prominence on initial echocardiogram. Three subsequently developed coronary artery dilatation all of whom had received IVIG during first week of fever. Three cases were transferred to tertiary centre for second–line management encompassing repeat IVIG (3/18), infliximab (2/18) and corticosteroids (1/18). Conclusion: Two thirds of KD cases were incomplete. Ninety–four percent had IVIG. Inflammatory markers, laboratory criteria and BCG scar change did not correspond with cardiovascular complications. Dose of aspirin given varied between 30–100 mg/kg/day depending on tertiary centre recommendation. All patients were managed appropriately. Those that failed to respond were referred to a tertiary centre. This study demonstrates most KD can be managed locally with adherence to clear guidelines and receiving tertiary advice when required. However clearer consensus on high–dose aspirin is needed.